Spinal subarachnoid diverticula in dogs: A review - Smith, Casey J. (Can Vet J, 2020)
Spinal subarachnoid diverticula are fluid dilations of the subarachnoid space that can cause a compressive myelopathy in dogs. These diverticula are usually associated with high motion areas in the cervical and caudal thoracic spine. The definitive etiopathogenesis has not been determined but likely involves congenital or acquired causes. Pugs, French bulldogs, and Rottweilers are overrepresented breeds. Clinical signs typically include ataxia, paresis, and upper motor neuron urinary and/or fecal incontinence; pain is a less common feature. Diagnosis is based on advanced imaging, with magnetic resonance imaging now being favored given the additional detail of the spinal cord parenchyma that can be obtained. Outcomes are better with surgical intervention than with medical therapies, though there is a lack of long-term data. No superior surgical technique has been identified, and questions remain on the significance of addressing leptomeningeal adhesions at the time of surgery. Clinical signs can recur, though not always due to recurrence of diverticulum formation, and pugs may be less likely to have a successful long-term outcome.